Complex integrated method of improvement of sports ballroom dance performance - V.I. Omelyanenko (Physical Education of Students, 2014)
Purpose: to elaborate complex integrated method of psychological influence upon sport ballroom dancers for their quick response to assumed mistakes by executing other steps in training mode in place of given compositions. Material: 20 senior sport ballroom dancers: 10 - experimental group, 10 - control group. At the I stage dancers for participation in the experimental group with regard to their hypnosis ability for facilitation teaching dynamic meditation were selected. Sportsmen with the 2 nd -3 rd stage of hypnosis were enrolled to the experimental group. At the II stage the experimental group was trained in the method of dynamic meditation. For this, the static meditation was performed first, after this the test persons opened their eyes and without leaving the achieved result with help of the static state of meditation, practiced in dynamic meditation. At the III stage training in sports ballroom dances with introduction new steps changing the composition program sequence to composition was held. The coach evaluated response of the test persons in the state of the dynamic meditation. Results: at the II stage of the research on training in dynamic meditation the dancers of the experimental group needed 3-7 repetitions. At the III stage of the research 8 test persons had trained to response adequately to changes in the compositions within 10-15 repetitions. In the control group if a partner changed steps during performance of the composition it led to stop of the dancing couple. For 8 test persons in the experimental group steps replacement didn’t affect adversely the quality of the dance. The senior group of dancers studied new steps with great difficulty, their motion stereotype was formed badly, they preferred to dance compositions trained earlier. The seniors having insufficient technical background (2 persons) showed low abilities, they had bad memory, they spent 3 months for mastering new compositions. Conclusions: The methods elaborated by us providing for inclusion in the training process stand-alone dance steps in place of compensation steps, provided development of the dancers’ ability to respond quickly to assumed mistakes during dance performance. Mastering dynamic meditation depended on typological features of the nervous system: the higher hypnosis ability degree the better mastering. Women-partners of the experimental group who had high hypnosis ability degree and mastered dynamic meditation could quickly adequately response to the rapid changes in the composition performed by dance partner during dance. Consideration of possible errors trains a woman-partner’s ability to switch timely from one step to another. Using this method, improvement of professional skills of dancers accelerates greatly.